Addressing the challenges of field notes in medical education: a qualitative study of resident experiences - Ryan S. Huang; Tushar Sood; Matthew Nelms; Lauren Wintraub; Fok-Han Leung (BMC Medical Education)
Abstract Background Evaluating resident physicians’ competencies is critical in medical education to ensure high standards of patient care and professional development. Field notes are increasingly used as reflective tools in postgraduate medical education. Despite their growing use, skepticism about their effectiveness persists. This study aims to identify challenges with learner engagement in field notes and gather suggestions for operational improvements. Methods A qualitative study was conducted in the Department of Family & Community Medicine at the University of Toronto. Semi-structured interviews were conducted with seven postgraduate year one and year two family medicine residents. The interviews focused on residents’ experiences and challenges with field notes. Data were analyzed using inductive thematic analysis to develop a comprehensive codebook, in alignment with Braun and Clarke’s framework. Results Several key challenges with the use of field notes were identified including the redundancy of feedback, sporadic utilization, and time constraints for preceptors. Residents also expressed uncertainty about the expectations for using the tool and identified it as complex and cumbersome. Operational suggestions for improvement included the development of a mobile-friendly platform, streamlined functionality, a standardized and integrated feedback system, and clearer guidelines for use. Conclusions The study highlighted significant challenges in the use of field notes within family medicine training programs and underscored the need for technological and procedural innovations to improve their effectiveness. Addressing these challenges through user-friendly design, clear guidelines, and integrated support systems could transform field notes into a more robust tool for competency-based medical education, benefiting residents, preceptors, and the broader medical community.